A two‐step method for predicting time to flashover in room corner test fires using cone calorimeter data. (27th June 2012) - Wang, Zhaozhi; Hu, Xiaoqin; Jia, Fuchen; Galea, Edwin R.
ABSTRACT A method to predict time to flashover in ISO 9705 room corner fire tests based on cone calorimeter data is proposed in this paper. The method involves classification of materials and estimation of time to flashover as two steps in sequence. In the first step, the investigated material is classified into discriminating material groups. In the second step, the time to flashover is calculated with a derived formula for the corresponding material group, which contains material density, time to ignition and heat release rate collected from small‐scale experiments. Compared with two existing models, the proposed method has improved the prediction precisions in both the time to flashover and classification of material categories for a wide range of materials. Copyright © 2012 John Wiley & Sons, Ltd.